Mortality risk of loneliness in the oldest old over a 10-year follow-up. (2nd January 2020) - Wang, Hanyuying; Leng, Yue; Zhao, Emily; Fleming, Jane; Brayne, Carol; ,
Abstract: Objective: To investigate the impact of loneliness on all-cause mortality in the oldest old population over a 10-year follow-up. Method: Participants were from the third wave of the Cambridge City over-75s Cohort (CC75C) study, a population-based longitudinal study of older people aged 75 or over. Loneliness was measured two further times. At each wave, participants were asked how often they felt lonely and the answers were divided into three levels: not lonely, slightly lonely and lonely. The relationship between loneliness and all-cause mortality was examined using Cox regression with loneliness as a time-varying predictor. The association was adjusted for socio-demographic factors, number of chronic diseases, functional ability and depression. Results: Seven hundred thirteen participants were seen at wave 3 (out of 2166 at baseline), of whom 665 had data on loneliness. The prevalence of feeling slightly lonely and lonely was 16% and 25%, respectively. Vital status was followed for a further 10 years. A total of 562 participants died during the follow-up. After adjusting for age, sex and other socio-demographic factors, loneliness was associated with a 20% increased risk of mortality (HR: 1.2, 95% CI: 1.0–1.6). The association was disappeared after further adjusting for health conditions and depression (HR: 1.0, 95% CI: 0.8–1.4). Individuals who reported being slightly lonely were not at risk of mortality. Conclusions: The association between loneliness and mortality was fully explained by health conditions, suggesting that in the very old age, health problem is the proximal risk factor for mortality.